KEANEKARAGAMAN JENIS TUMBUHAN PENYUSUN VEGETASI LANTAI LINGKUNGAN QUARRY DI KAWASAN PENAMBANGAN EMAS TRADISIONAL, SEKOTONG, LOMBOK BARAT - , HENDRO KUSUMO EKO PRASETYO MORO, Dr. RIna Sri Kasiamdari ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Traditional gold mining causes damage to habitat and vegetation. The diversity of floor vegetation can be disturbed by the presence of tailings dumped in the quarry from maining activities. The aim of this study were to know and study the diversity of plant species growing around the quarry